A Case Report of Steroid Responsive Nivolumab-Induced Encephalitis. (21st December 2017) - Richard, Kaja; Weslow, Jacqueline; Porcella, Stephanie L.; Nanjappa, Sowmya
Nivolumab (Opdivo) approval for the treatment of non-small cell lung cancer (NSCLC) prompts recognition of its future use in various cancers. Although rare, occurring in 1% to 3% of treated cases, nivolumab along with other immune checkpoint inhibitors are associated with immune-related encephalitis. With its prospective use, nivolumab-induced encephalitis illustrates the necessity of early recognition and successful management to decrease morbidity and mortality. We describe a treated case of nivolumab-induced encephalitis. A 74-year-old male with a history of stage 4 squamous NSCLC presenting with insidious altered mental status following his first dose of nivolumab. After an extensive workup that proved negative, the patient received intravenous steroids with gradual improvement of mental status. Patient subsequently returned to baseline and was discharged with oral steroid taper. Nivolumab-induced encephalitis is a diagnosis of exclusion with nonspecific signs and symptoms. Immediate recognition of patients prescribed nivolumab chemotherapy could potentially prevent fatal complications of neurotoxicity.